Depression and pain: testing of serial multiple mediators - Wongpakaran T; Wongpakaran N; Tanchakvaranont S; Bookkamana P; Pinyopornpanish M; Wannarit K; Satthapisit S; Nakawiro D; Hiranyatheb T; Thongpibul K (Neuropsychiatric Disease and Treatment)
Tinakon Wongpakaran,1 Nahathai Wongpakaran,1 Sitthinant Tanchakvaranont,2 Putipong Bookkamana,3 Manee Pinyopornpanish,1 Kamonporn Wannarit,4 Sirina Satthapisit,5 Daochompu Nakawiro,6 Thanita Hiranyatheb,6 Kulvadee Thongpibul7 1Department of Psychiatry, Faculty of Medicine, Chiang Mai University, Chiang Mai, Kingdom of Thailand; 2Department of Psychiatry, Queen Savang Vadhana Memorial Hospital, Chonburi, Kingdom of Thailand; 3Department of Statistics, Faculty of Science, Chiang Mai University, Chiang Mai, Kingdom of Thailand; 4Department of Psychiatry, Faculty of Medicine, Siriraj Hospital, Mahidol University, Bangkok, Kingdom of Thailand; 5Department of Psychiatry, Khon Kaen Regional Hospital, Khon Kaen, Kingdom of Thailand; 6Department of Psychiatry, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Kingdom of Thailand; 7Department of Psychology, Faculty of Humanities, Chiang Mai University, Chiang Mai, Kingdom of Thailand Purpose: Despite the fact that pain is related to depression, few studies have been conducted to investigate the variables that mediate between the two conditions. In this study, the authors explored the following mediators: cognitive function, self-sacrificing interpersonal problems, and perception of stress, and the effects they had on pain symptoms among patients with depressive disorders.Participants and methods: An analysis was performed on the data of 346 participants with unipolar depressive disorders. The 17-item Hamilton Depression Rating Scale, Mini-Mental State Examination, the pain subscale of the health-related quality of life (SF-36), the self-sacrificing subscale of the Inventory of Interpersonal Problems, and the Perceived Stress Scale were used. Parallel multiple mediator and serial multiple mediator models were used. An alternative model regarding the effect of self-sacrificing on pain was also proposed.Results: Perceived stress, self-sacrificing interpersonal style, and cognitive function were found to significantly mediate the relationship between depression and pain, while controlling for demographic variables. The total effect of depression on pain was significant. This model, with an additional three mediators, accounted for 15% of the explained variance in pain compared to 9% without mediators. For the alternative model, after controlling for the mediators, a nonsignificant total direct effect level of self-sacrificing was found, suggesting that the effect of self-sacrificing on pain was based only on an indirect effect and that perceived stress was found to be the strongest mediator.Conclusion: Serial mediation may help us to see how depression and pain are linked and what the fundamental mediators are in the chain. No significant, indirect effect of self-sacrificing on pain was observed, if perceived stress was not part of the depression and/or cognitive function mediational chain. The results shown here have implications for future research, both in terms of testing the model and in clinical application. Keywords: depressive disorder, mediator, serial mediation, multiple mediation